The Effect of The Use of Audio Types of Learning Media on Students' Learning Motivation in Social Studies Subjects - Edo Suhariyanto (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2020)
ABSTRACT One of the learning media that has been successfully developed to have a positive and significant impact on student motivation is the use of audio learning media. The formulation of the problem in this research is "Is there a Positive and Significant Effect of Using Learning Media Types of Audio on Student Motivation in Social Studies Subjects in Class VII of SMP Negeri 17 Bandar Lampung in the 2019/2020 Academic Year." The purpose of this study was to determine the positive and significant influence of the use of audio-type learning media on student learning motivation in social studies subjects in class VII SMP Negeri 17 Bandar Lampung for the 2019/2020 academic year. This study used a Posttest-Only Control Design research design. The population in this study were all seventh grade students at SMP Negeri 17 Bandar Lampung in the 2019/2020 school year. Samples were selected randomly using the Random technique. The data analysis technique in this research is quantitative data analysis by means of data analysis with the Theta formula. Based on quantitative data analysis using the Theta formula, it can be concluded that "There is a positive and significant influence which is quite significant or moderate, namely 0.41 from the use of audio-type learning media on student learning motivation in social studies subjects for class VII SMP N 17 Bandar Lampung in the academic year. 2019/2020. Keyword: Influence, Model, Audio, Learning Motivation Doi: http://dx.doi.org/10.23960/pesagi.v8.i2.2020.01